2011
DOI: 10.1063/1.3639272
|View full text |Cite
|
Sign up to set email alerts
|

Polariton laser based on a ZnO photonic crystal slab

Abstract: We propose a scheme of a ZnO room-temperature polariton laser based on a photonic crystal slab. We predict a very low threshold density for optical pumping: 5 × 1016 cm−3. We have studied the threshold dependence on the parameters of the system, such as detuning. The main advantage of photonic-crystal-based polariton laser is expected to be the simplicity of production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The polaritons can also be confined in 0D-traps [58]. Increasing the complexity of the photonic structures, the actual realization of a photonic crystal allowing a stronger control of the photonic bands [105,106] is still very challenging. Their equivalents with ZnO nanowire polariton lasers have however been successfully realized: a trap compatible with an evaporative cooling of the polariton condensate was recently demonstrated [107], as well as a periodic modulation of the polariton bands [52] and the coupling to ring resonators [86].…”
Section: ) Towards 300k Polariton Devicesmentioning
confidence: 99%
“…The polaritons can also be confined in 0D-traps [58]. Increasing the complexity of the photonic structures, the actual realization of a photonic crystal allowing a stronger control of the photonic bands [105,106] is still very challenging. Their equivalents with ZnO nanowire polariton lasers have however been successfully realized: a trap compatible with an evaporative cooling of the polariton condensate was recently demonstrated [107], as well as a periodic modulation of the polariton bands [52] and the coupling to ring resonators [86].…”
Section: ) Towards 300k Polariton Devicesmentioning
confidence: 99%
“…This approach can be easily extended to larger supercells in order to investigate the influence of disorder on the optical properties in periodic micro-and nanostructures [51,52]. Furthermore, it has been shown that controlling the superperiodicity allows for tailoring the optical properties of photonic crystal slabs [53].…”
Section: Introductionmentioning
confidence: 99%
“…They behave like bosonic quasiparticles at moderate concentrations ( 10 11 cm −2 ). Due to their small effective mass, exciton polaritons can manifest quantum coherent properties up to room temperature in wide-band-gap materials [10,11]. Exciton-polariton qBEC emerges as the result of boson-boson interactions and energy exchange with the environment.…”
Section: Introductionmentioning
confidence: 99%